2007
DOI: 10.1007/s10490-006-9030-3
|View full text |Cite
|
Sign up to set email alerts
|

Performance implications of nonmarket strategy in China

Abstract: Nonmarket strategy may have positive influences on a firm’s performance. How does nonmarket strategy influence a firm’s performance? This article addresses this important question by introducing two mediators: corporate social performance and adaptive capability. The empirical results based on a survey of 438 usable questionnaires from China indicate that “buffering” and “bridging,” being two kinds of nonmarket strategies, have a positive impact on a firm’s economic performance through enhancing its social per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(53 citation statements)
references
References 80 publications
(88 reference statements)
2
51
0
Order By: Relevance
“…Similar to previous studies (He, Tian & Chen, 2007;Lu et al, 2010;Woodcock, Beamish & Makino, 1994), this study adopted the same perceptual measure for the subsidiary performance of Chinese MNEs. This self-evaluation approach was appropriate because (1) firms were either unwilling or unable to provide sensitive accounting data (e.g.…”
Section: Dependent Variablementioning
confidence: 99%
See 1 more Smart Citation
“…Similar to previous studies (He, Tian & Chen, 2007;Lu et al, 2010;Woodcock, Beamish & Makino, 1994), this study adopted the same perceptual measure for the subsidiary performance of Chinese MNEs. This self-evaluation approach was appropriate because (1) firms were either unwilling or unable to provide sensitive accounting data (e.g.…”
Section: Dependent Variablementioning
confidence: 99%
“…Although difficulties such as self-enhancement and objectivity might be encountered, self-evaluated surveys have been proved to possess strong internal consistency and reliability (Cooper & Artz, 1995;Ketokivi & Schroeder, 2004) and have been widely used in previous studies (Andersson, Forsgren & Holm, 2002;Birkinshaw, Hood & Young;He et al, 2007;Lu et al, 2010).…”
Section: Dependent Variablementioning
confidence: 99%
“…He, Tian, & Chen, 2007;Roman, Hayibor, & Agle, 1999;Waddock & Graves, 1997) and the sustainability of above average profitability (Roberts & Dowling, 2002). This result is, however, equivocal.…”
Section: Firm Industry and Network Antecedents Of Corporate Social Permentioning
confidence: 99%
“…The detailed information on subsidiary locations is presented in Table 1. & Xu, 2002;He, Tian, & Chen, 2007;Lu, et al, 2010), a perceptual measure was used to proxy the performance of overseas subsidiaries of Chinese MNEs. Some researchers (He, Tian, & Chen, 2007;Woodcock, Beamish, & Makino, 1994) indicated that perceptual measures are appropriate when (1) companies are either unwilling or unable to provide sensitive accounting data; (2) variations in accounting approaches across countries is likely to hinder the reconciliation of differences; and/or (3) there are fluctuations in exchange rates between home and host countries.…”
Section: Sample and Data Collectionmentioning
confidence: 99%
“…& Xu, 2002;He, Tian, & Chen, 2007;Lu, et al, 2010), a perceptual measure was used to proxy the performance of overseas subsidiaries of Chinese MNEs. Some researchers (He, Tian, & Chen, 2007;Woodcock, Beamish, & Makino, 1994) indicated that perceptual measures are appropriate when (1) companies are either unwilling or unable to provide sensitive accounting data; (2) variations in accounting approaches across countries is likely to hinder the reconciliation of differences; and/or (3) there are fluctuations in exchange rates between home and host countries. As a widely used construct in previous studies (Andersson, Forsgren, & Holm, 2002;Birkinshaw, Hood, & Young, 2005;He, Tian, & Chen, 2007;Lu, et al, 2010), perceptual measures of performance have been proved to possess strong internal consistency and reliability (Cooper & Artz, 1995;Ketokivi & Schroeder, 2004).…”
Section: Sample and Data Collectionmentioning
confidence: 99%